APLIKASI THEORY OF UNPLEASANT SYMPTOMS (TOUS) PADA ANAK YANG MENGALAMI NYERI DI RUANG RAWAT NON INFEKSI RSCM JAKARTA - Andin Sefrina; Nani Nurhaeni; Happy Hayati (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to illustrate the application of the Theory of Unpleasant Symptoms (TOUS) in children who experience nausea caused by chemotherapy and analyze their effectiveness. TOUS has three components: symptoms, factors affecting the client and the final appearance.  Methods: The application process begins with an analysis of the theory, preparation of nursing care format of assessment and evaluation, implementation of the application of theory to the three clients and analyzing the effectiveness of the use of theory. Results: Results of the implementation of applications, namely TOUS theory can be applied to the nursing care of children who have cancer pain and pain related to diagnostic procedures for the management of symptoms through TOUS based, needs a sense of comfort the child will be met despite the pain they still appear for hospitalized children.  Conclusion: Application TOUS on nursing care to children should pay attention to the psychological aspects of growth and development and child. Both aspects are proven to affect the shape of pain and symptom management may affect the implementation of nursing care in general.